2021
DOI: 10.1016/j.ultsonch.2021.105654
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound extraction optimization for bioactive molecules from Eucalyptus globulus leaves through antioxidant activity

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…The results showed that the two essential oils of the plants studied had good antioxidant activity. And, increasingly, research on biological antioxidants is focusing on E. globulus [27–30] . However, the essential oil of L. multiflora was more active against DPPH than that of E. globulus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the two essential oils of the plants studied had good antioxidant activity. And, increasingly, research on biological antioxidants is focusing on E. globulus [27–30] . However, the essential oil of L. multiflora was more active against DPPH than that of E. globulus .…”
Section: Discussionmentioning
confidence: 99%
“…And, increasingly, research on biological antioxidants is focusing on E. globulus. [27][28][29][30] However, the essential oil of L. multiflora was more active against DPPH than that of E. globulus. These results confirm those of Harkat-Madouri et al [31] who revealed that the essential oil of E. globulus leaves collected in Algeria possessed a very low antioxidant capacity towards DPPH.…”
Section: Discussionmentioning
confidence: 99%
“…A significant decrease is observed when methanol and methanol combined with water are used ( Table 2 ). This suggests that the water affects the capacity to extract these compounds, in comparison with the pure solvent, and that the ethanol is more akin to the extraction of the phenolic compounds present in eucalyptus [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…A Box-Bohnken (B-B) design was used in optimizing the pomegranate flower extraction parameters [24] , [25] , [26] . Different factors with high and low levels are shown in Table S1 .…”
Section: Methodsmentioning
confidence: 99%